DOP51 Biomarker and pharmacokinetic data from the TURANDOT II open-label extension study of the anti-mucosal addressin cell adhesion molecule-1 (MAdCAM-1) antibody SHP647 in patients with ulcerative colitis. (25th January 2019) - Reinisch, W; Sandborn, W J; Danese, S; Hébuterne, X; Kłopocka, M; Tarabar, D; Vaňásek, T; Greguš, M; Hellstern, P A; Kim, J S; Sparrow, M; Gorelick, K J; et al.
Abstract: Background: SHP647, a fully human IgG2 monoclonal antibody, binds to human mucosal addressin cell adhesion molecule-1 (MAdCAM-1) thus reducing lymphocyte homing to the gastrointestinal tract. Results from the Phase 2, extension study TURANDOT II (NCT01771809) showed that SHP647 was well tolerated for up to 144 weeks and resulted in continued clinical benefit in patients with moderate-to-severe ulcerative colitis (UC). This analysis from the TURANDOT II trial reports biomarker and pharmacokinetic (PK) data from the first 72 weeks of the study. Methods: TURANDOT II was a Phase 2, multi-centre, 2-part open-label (OL) study of SHP647 in patients with moderate-to-severe UC who completed TURANDOT on placebo or SHP647 7.5, 22.5, 75, or 225 mg s.c. every 4 weeks. At TURANDOT II baseline, patients were randomised to SHP647 75 or 225 mg s.c. every 4 weeks for 72 weeks (OL part 1). Dose escalation from 75 to 225 mg was permitted at the investigator's discretion at any time from 8 to 72 weeks in the event of clinical exacerbation or no treatment response. In OL part 2, all patients received 75 mg every 4 weeks for a further 72 weeks. In OL part 1, high-sensitivity C-reactive protein (hsCRP) and faecal calprotectin (FCP) were analysed every 4 weeks until Week 24, and then at 32 and 72 weeks. Soluble MAdCAM-1 levels were measured at Weeks 0 and 16, and plasma SHP647 concentrations were measured every 4 weeks. No biomarker or PK data were collected in OL part 2. Results: Of the 330 patients treated, 329 were included in the pharmacodynamic population (SHP647 75 mg, n = 163; SHP647 225 mg, n = 166). Two patients in the 225 mg dose group were not included in the PK population. FCP and hsCRP levels reduced consistently over the 72 weeks of OL part 1 in both dose groups (Figures 1 and 2). Mean plasma concentrations of SHP647 increased dose-dependently. Geometric mean soluble MAdCAM-1 concentrations were lower in both dose groups at Week 16 vs. baseline, with changes of –74%, –86%, and –81% in the 75 mg, 225 mg, and total groups, respectively. Conclusions: This analysis of data from the TURANDOT II study shows that SHP647 treatment is associated with a reduction in biomarkers specific to its mode of action, as well as long-term reductions in inflammatory biomarkers.